2011
DOI: 10.1292/jvms.10-0243
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Florfenicol-Tylosin Combination after Intravenous and Intramuscular Administration to Beagle Dogs

Abstract: ABSTRACT. A pharmacokinetic study of a commercial florfenicol-tylosin (2:1) combination product was conducted in six beagle dogs after intravenous (IV) and intramuscular (IM) administration at doses of 10 mg/kg (florfenicol) and 5 mg/kg (tylosin). Serum drug concentrations were determined by a validated high performance liquid chromatography (HPLC) using UV detection. A rapid and nearly complete absorption of both drugs with a mean IM bioavailability of 103.9% (florfenicol) and 92.6% (tylosin), prolonged elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
(33 reference statements)
3
10
2
1
Order By: Relevance
“…The variation in the pharmacokinetic parameters of florfenicol observed in this study might be due to differences in the dose and in the methods used for pharmacokinetic analysis. The volume of distribution and prolonged terminal half-lives of tylosin found after administration of the mixture were comparable to our previous findings in beagle dogs (Kim et al 2011). In contrast, other studies have shown that serum concentrations of tylosin fell rapidly after i.m.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The variation in the pharmacokinetic parameters of florfenicol observed in this study might be due to differences in the dose and in the methods used for pharmacokinetic analysis. The volume of distribution and prolonged terminal half-lives of tylosin found after administration of the mixture were comparable to our previous findings in beagle dogs (Kim et al 2011). In contrast, other studies have shown that serum concentrations of tylosin fell rapidly after i.m.…”
Section: Discussionsupporting
confidence: 91%
“…administration of the FTD mixture was lower than that reported in previous studies following high-dose injection of the mixture in beagle dogs (Kim et al 2011) and after administration of florfenicol alone to dogs and other species of animals (Ali et al 2003;Jiang et al 2006;Park et al 2008). Similarly, the average volume of distribution of florfenicol was slightly lower than our previous value of 2.6 l/kg, which was obtained after administering a high-dose FTD mixture to the same animal species.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations